Building Creativity Student through Portfolio Model-Based Learning Subject Civic Education - Agung Kurniawan (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
The purpose of this research is to develop creativity using portable-based learningmethod. The study is development research using classroom action research principle.This research uses three research cycles. In the first cycle Average students' creativethinking ability in Lead cycle 24.28%. The average student attendance in educationalactivities in the first cycle was 32.5%. In the second cycle, the average increase instudent effectiveness in cycle II of 48.47%. The average student attendance in thelearning activity in the second cycle was 47.5%. In cycle three addition, the ability willbe used in a high category that is equal to 75,71%, student participation in learningactivity included in the good category, that is equal to 82%. Thus it can be concludedthat the learning portfolio can improve students' creative thinking ability.